Legalising Local Wisdom: The Bersik Kali Tradition and Community Participation in Karst River Conservation for SDG 15 - Rita Bekti Utami; Slamet Suyanto; Suhartini; Insih Wilujeng; Yudan Hermawan; Chairul Agus Mantara (International Journal of Law and Society, 2026)
River ecosystem degradation caused by pollution and increasing anthropogenic pressure requires culturally grounded and community-based conservation approaches. This study aims to analyse the cultural foundations and ecological functions of the Bersik Kali tradition in supporting community-based river conservation in the karst area of Goa Pindul, Bejiharjo Village, examine its role in enhancing community participation in river ecosystem protection, and assess its alignment with environmental law and SDG 15. Using a qualitative case-study design, data were collected through participant observation, in-depth interviews, and documentation analysis. Data were analysed using Miles, Huberman, and Saldana's interactive model data condensation, display, and conclusion drawing, while data validity was ensured through triangulation of techniques, sources, and time. The findings reveal that Bersik Kali serves as an effective culturally rooted mechanism for strengthening ecological awareness, participation, and shared responsibility for river conservation. Beyond improving river cleanliness, the tradition contributes to karst ecosystem functions by enhancing water infiltration, stabilising flow into underground channels, and supporting riparian vegetation recovery. Additional findings show that customary norms, social sanctions, and informal leadership play crucial roles in complementing formal environmental regulations and addressing implementation gaps in local river conservation governance in line with SDG 15. Collaboration with local government and environmental organisations further reinforces program sustainability despite persistent challenges such as waste-disposal habits, limited infrastructure, and uneven legal awareness. The study offers an original contribution by proposing a culturally grounded participatory conservation model that integrates Local Ecological Knowledge, ritual practices, ecological actions, and legal frameworks into a unified system of river and karst management. However, the study is limited to a single tradition and geographic setting, suggesting the need for comparative research across different cultural conservation practices.